Evaluation of the Prevalence, Regional Phenotypic Variation, Comorbidities, Risk Factors, and Variations in Response to Different Therapeutic Modalities Among Indian Women: Proposal for the Indian Council of Medical Research–Polycystic Ovary Syndrome (ICMR–PCOS) Study - Ganie, Mohd Ashraf; Chowdhury, Subhankar; Suri, Vanita; Joshi, Beena; Bhattacharya, Prasanta Kumar; Agrawal, Sarita; Malhotra, Neena; Sahay, Rakesh; Rozati, Roya; Jabbar, Puthiyaveettil Khadar; Sreenivas, Vishnubhatla; Sriwastva, Mukesh; et al. (JMIR research protocols, 2021)
There is scanty data in India on polycystic ovary syndrome (PCOS) from several small, undersized, convenience-based studies employing differing diagnostic criteria and reporting varied regional prevalence. It is difficult to draw clear-cut conclusions from these studies; therefore, the present multicentric, well-designed, large-scale representative countrywide epidemiological study on PCOS across India was conceived with the aim to generate the actual prevalence rates of PCOS in India with a total sample size of approximately 9000 individuals. The primary objectives of the study are to estimate the national prevalence of PCOS in India and the burden of comorbidities and to compare the variation in efficacy of standard therapeutic modalities for metabolic dysfunction in women with PCOS. This multicentric umbrella study consists of three different substudies. Substudy 1 will involve recruitment of women aged 18-40 years using a multistage sampling technique from randomly selected polling booths across urban and rural areas to estimate national prevalence, phenotypic variation, and risk factors among regions. Substudy 2 involves recruitment of subjects from the community pool of substudy 1 and the institutional pool for quantitation of comorbidities among women with PCOS. Substudy 3, an interventional part of the study, aims for comparison of variation in efficacies of common treatment modalities and will be conducted only at 2 centers. The eligible consenting women will be randomized in a 1:1 ratio into 2 arms through a blinding procedure. All these women will undergo clinical, biochemical, and hormonal assessment at baseline and at 3 and 6 months. The data generated will be analyzed using the reliable statistical software SPSS (version 26). The study is ongoing and is likely to be completed by April 2022. The data will be compiled and analyzed, and the results of the study will be disseminated through publications. The Indian Council of Medical Research-PCOS study is the first of its kind attempting to provide accurate and comprehensive data on prevalence of PCOS in India. Clinical Trials Registry-India CTRI/2018/11/016252; ctri.nic.in/Clinicaltrials/pmaindet2.php?trialid=26366. DERR1-10.2196/23437.